Typical characteristics of deep coal seams with high outburst risk, outburst inducing mechanism and prevention measures - Baiquan LIN; Wei YANG; Tong LIU (Meitan xuebao)
Coal mining in China has gradually entered deep levels. With the continuous increase in mining depth, the outburst risk of coal seam has significantly increased, with both the frequency and intensity of outbursts rising noticeably, posing huge challenges to the safe and efficient development of deep coal resources. This paper first analyzes the complex stress environment faced by coal seams at different depths in deep areas, then systematically studies the typical characteristics of high-risk coal seams in deep regions, elucidates the mechanisms of outburst induction in deep mining, and finally proposes countermeasures for preventing outburst disasters in deep mining. The research indicates that for outburst coal seam mining, there is no fixed depth in deep areas, but rather a nonlinear mechanical state of coal seams influenced by factors such as stress, gas pressure, and coal body strength. In deep coal seams, stress is high, and coal undergoes strong plastic deformation when mined. The porosity of outburst coal is low, with poor connectivity, and under high stress, the permeability of the coal seam is extremely low. High-pressure gas is highly saturated in the coal seam, with strong adsorption capacity at low pressure levels. The matrix of the coal has a large scale and poor permeability, making gas migration across scales difficult. The maximum horizontal principal stress in the deep coal seams is increasing, and under strong tectonic stress, the degree of coal fragmentation is high. This leads to the formation of high-pressure gas pockets within the areas of concentrated tectonic stress, resulting in a significant increase in outburst risk. When encountering structural soft coal ahead of the mining face in deep areas, strong stress concentration is more likely to form within the nearby hard coal, which significantly enhances the sealing effect of high-pressure gas within the structural soft coal, resulting in a high gas pressure and large gradient in front of the workings. This makes the gas expansion energy within the coal significantly higher than that in the shallow part. Additionally, under high stress conditions, the coal body ahead of the woking face is more likely to undergo strong plastic rheological damage, which induces the violent release of deformation energy. Due to the large deformation damage of the tectonic coal body, the pore and fracture space increases; at the same time, the matrix scale decreases sharply, and a large amount of enclosed gas is rapidly desorbed. The two together cause the synchronized rapid increase of free gas storage space and gas pressure, which triggers the rapid increase of free gas expansion energy. When the gas expansion energy is higher than the protrusion threshold, a large amount of gas will be broken and thrown out of the coal body, leading to the occurrence of outburst accidents. Based on this, the authors propose that the prevention and control of outburst disasters in deep areas should focus on rationalizing mining layouts to reduce localized stress concentrations during mining. Furthermore, by proactively detecting and accurately obtaining key information such as concealed coal structure, coal-rock mechanics parameters, and gas parameters, the early identification of outburst risks can be achieved and precise preventive measures can be implemented. It is emphasized that stress should be fully relieved through depth unloading to reduce stress concentrations in coal seams, improve coal seam permeability, and induce the desorption of large amounts of low-pressure adsorbed methane. Additionally, it is recommended to reduce reduce the matrix scale and accelerate gas migration by strong seaming and permeability enhancing technology. Furthermore, through a physical-chemical combined enhancement method, activating matrix pores, building cross-scale flow channels between matrix pores and fractures, improving gas extraction efficiency, significantly reducing gas content in coal seams, and ultimately achieving the goal of advanced, precise, efficient, and uniform outburst prevention, and enabling safe and efficient exploitation of deep coal seams with high outburst risks.